Impact of Staff Competencies and Organizational Culture on Service Performance of Local Government: Mediating Role of Organizational Innovativeness - Imaniyati, Nani; Ramdhany, Muhamad Arief; Santoso, Budi; Hadijah, Hady Siti; Nurjanah, Santi (Jurnal Cakrawala Pendidikan, 2024)
This study proposes a model of service performance of local government influenced by staff competencies and organizational culture and mediated by organizational innovativeness. This is an empirical study using quantitative approach and a descriptive survey method to get the data from 130 staffs of the local government office as respondents. Data were collected through questionnaire and analyzed using Partial Least Square (PLS). The findings of this study are (1) organizational innovativeness is positively affected by staff competencies and organizational culture, (2) service performance is positively affected by staff competencies, organizational culture, and organizational innovativeness, (3) organizational innovativeness can serve as mediating variable for the relationship between staff competencies and service performance, also for the relationship between organizational culture and service performance. This study fulfills an understanding of the impact of staff competencies and organizational culture on the service performance of local government, mediated by organizational innovativeness.